DAMPAK KEBERADAAN MINIMARKET ALFAMART BAGI WARUNG TRADISIONAL - Amelia, Pipi; Hardiansyah, Muhammad Agus (Universitas Tanjungpura, 2022)
This study aims to analyze the impact of the existence of minimarkets Alfamart on the people of Sindangsari Village and for traditional stalls in Sindangsari village, what factor affect the changes in tradisional stalls, what strategies are carried out by traditional stalls to keep their businesses running and earning income. The research method used is qualitative with a descriptive method. This research method will describe the problems and conditions after the existence of the minimarket Alfamart in Sindangsari village. Data collection methods used are observation, interview, and documentation. The data collected in this study are primary data and secondary data. The results of this study explain that the existence of Alfamart has resulted in many changes, especially economic changes. The life of the Sindangsari Village community is not the same as usual, but there are many changes that occur starting with behavior, activity, lifestyle, and others. This certainly shifts the social system and the usability of the Sindangsari Village community. For traditional stalls, the existence of a minimarket Alfamart is a threat that can lead to a decline in their business, and the shop may even be closed due to losing competitiveness. The existence of a minimarket Alfamart makes traditional stalls have to struggle more with strategies of all kinds of ways to be done so that their business can continue to run and earn income to meet their daily needs.